Islamic reformism in Malaya: the case of Syed Sheikh al-Hadi - Zakariya, Hafiz (2018)
The period of the late 19th to the early 20th centuries witnessed the emergence Islamic reformism in Malaya. Against the background of Malay backwardness the reformists believe that it is imperative for them to carry out a reform in their own society to redress the problems confronting them. In doing so, they believed that restoration of the purity of Islamic teachings and practices are necessary for the Muslims to get out from the material slump, and intellectual stagnation. A prominent Malay reformist who played a pivotal role in promoting the Islamic reformism in Malaya was Sayyid Shaykh Ahmad al-Hadi (hereafter, al-Hadi). Indeed, al-Hadi was the most effective reformist writer, propagandist and polemicist. Moreover, he enjoys a reputation as the father of the Malay novel, a progressive thinker and brilliant social critic.